Influence of Pesticide Intoxication Education on Farmer Knowledge and Attitude in Kalidoni District, Palembang City, Indonesia - Thia Prameswarie; Dientyah Nur Anggina; Camelia Panache; Florence Triningtyas (Faculty of Medicine, Universitas Padjadjaran, 2022)
Knowledge and attitude of farmers are among factors that influence pesticide intoxication in farms. They are influenced by several variables, including education. Farmers’ knowledge and attitude on pesticide intoxication may change after they receive interventions, such as education about pesticides. This study aimed to determine the level of knowledge and attitude of farmers on pesticide intoxication before and after an education session on pesticides in Sei Selincah Sub-district, Kalidoni District. This was a quasi-experimental observational analysis with a two-group pretest posttest design with a control group. This study used primary data from farmers in Sei Selincah Sub-district, Kalidoni District. Sampling was performed using the purposive sampling method and seventy-six respondents who met the inclusion and exclusion criteria were recruited. Results of the statistical tests using the Wilcoxon test showed that there was no difference in the level of knowledge and attitude of farmers before and after education, both fort the intervention group and the control group (p>0.05). Thus, education does not influence the level of knowledge and attitude on pesticides and pesticide intoxication among farmers.